The fire ascending - D'Lacey, Chris (Last dragon chronicles ;, 2012)
Young Agawin, apprentice to the healer Yolen, finds that his life is linked to that of the last of the dragons of the Wearle of Hautuuslanden, Galen, and he must journey far in time and space to protect the future of dragon-kind.